Sinergitas Pengembangan Infrastruktur Jalan dan Pembangunan Ekonomi Lokal Masyarakat Muslim di Kabupaten Pekalongan - Laila Fitria Nur Rahma; Ahmad Anas (SIL'AH: Jurnal Ekonomi Syariah, 2025)
This study aims to describe the synergy between road infrastructure development and the Village-Owned Enterprise program in the local economic development of the Muslim community in Menjangan Village, Pekalongan Regency. Using a qualitative research method with a descriptive analytical approach, this study employs field observations and interviews. The results of the study indicate that despite the poor condition of road infrastructure in Menjangan Village and the Village-Owned Enterprise experiencing a vacuum due to management constraints, the synergy between these two factors has the potential to create a conducive environment for business development and the village economy. This can be seen from the fact that improved road infrastructure can enhance access to markets and resources, while a well-functioning Village-Owned Enterprise can drive local economic development through sustainable local business initiatives. This study provides a paradigmatic contribution to policymakers in planning effective strategies to accelerate economic growth and reduce infrastructure gaps at the village level.